2019
DOI: 10.1002/cne.24762
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin and ErbB expression is regulated by development and sensory experience in mouse visual cortex

Abstract: Neuregulins (NRGs) are protein ligands that impact neural development and circuit function. NRGs signal through the ErbB receptor tyrosine kinase family. NRG1/ErbB4 signaling in parvalbumin-expressing (PV) inhibitory interneurons is critical for visual cortical plasticity. There are multiple types of NRGs and ErbBs that can potentially contribute to visual cortical plasticity at different developmental stages. Thus, it is important to understand the normal developmental expression profiles of NRGs and ErbBs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Multiple intracellular and extracellular agents are involved in cortical plasticity during the critical period, such as the activation of tissue plasminogen activators, endocannabinoids, orthodenticle homeobox 2 (Otx2), neuregulin, extracellular signal-regulated kinase 1,2 (ERK1/2) and epigenetic factors, whereas plasticity is inhibited by such agents as perineuronal nets, myelin and Nogo receptors [4,5,30]. These agents have been well characterized in the murine visual cortex, but little studied in the rat visual cortex or the respiratory system.…”
Section: Timing Of the Critical Periodmentioning
confidence: 99%
“…Multiple intracellular and extracellular agents are involved in cortical plasticity during the critical period, such as the activation of tissue plasminogen activators, endocannabinoids, orthodenticle homeobox 2 (Otx2), neuregulin, extracellular signal-regulated kinase 1,2 (ERK1/2) and epigenetic factors, whereas plasticity is inhibited by such agents as perineuronal nets, myelin and Nogo receptors [4,5,30]. These agents have been well characterized in the murine visual cortex, but little studied in the rat visual cortex or the respiratory system.…”
Section: Timing Of the Critical Periodmentioning
confidence: 99%
“…Exogenous NRG1 blocks the reduction in binocular PV interneuron responses. The expression of NRG1 in PV interneurons is developmentally regulated 11,15 . Its expression in the visual cortex starts high in early development, remains high during the juvenile critical period but decreases significantly in the adult cortex.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting reduction in PV cell activity is necessary for the subsequent reorganization of the excitatory circuit 10,11 . The level of NRG1 within PV interneurons peaks during the early juvenile development but gradually decreases as the cortex matures 11,15 . These results suggest that NRG1/ErbB4 signaling may be involved in juvenile cortical plasticity.…”
mentioning
confidence: 99%
“…It is affected by a family of epidermal growth factor domain‐containing receptor ligands that are expressed in the nervous system, and NRG1 is best characterized among these. [ 15 ] Several studies have shown that the NRG1/ErbB4 signaling pathway in PV inhibitory interneurons is critical for the activation of visual cortex plasticity. It controls the excitatory synaptic input to PV neurons so that PV‐cell‐mediated cortical disinhibition can occur after visual deprivation.…”
Section: Discussionmentioning
confidence: 99%